1996
DOI: 10.1063/1.117680
|View full text |Cite
|
Sign up to set email alerts
|

Near ultraviolet luminescence of Be doped GaN grown by reactive molecular beam epitaxy using ammonia

Abstract: Be doped GaN films grown by reactive molecular beam epitaxy (MBE) are investigated. The room temperature photoluminescence spectrum of the films that were studied shows features in the 390–420 nm range, similar to those observed in Mg doped GaN films, and indicates that Be can form acceptor states about 250 meV above the valence band of GaN. This is in contrast to previous works on GaN:Be films where the only luminescence feature seen was a broad peak centered at 2.16 eV (560 nm). Hot probe measurement indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 11 publications
2
29
1
2
Order By: Relevance
“…Experimental results about Be are inconclusive: Brandt et al have reported high levels of p-type doping using Be in MBE, provided oxygen is present as a co-dopant. 52,53 This result is difficult to understand based on equilibrium thermodynamics, as pointed out by Bernardini et al 50 Other work has indicated Be indeed acts as an acceptor; results about the ionization energy are based on luminescence, with Salvador et al finding a relatively large ionization energy (250 meV), 54 Ronning et al finding 150 meV, 55 and Sánchez et al deriving a much smaller value (90 meV). 56 To our knowledge, experimental studies of other acceptor impurities have only been performed using ion implantation (see, e.g., Ref.…”
Section: Alternative Acceptorsmentioning
confidence: 84%
“…Experimental results about Be are inconclusive: Brandt et al have reported high levels of p-type doping using Be in MBE, provided oxygen is present as a co-dopant. 52,53 This result is difficult to understand based on equilibrium thermodynamics, as pointed out by Bernardini et al 50 Other work has indicated Be indeed acts as an acceptor; results about the ionization energy are based on luminescence, with Salvador et al finding a relatively large ionization energy (250 meV), 54 Ronning et al finding 150 meV, 55 and Sánchez et al deriving a much smaller value (90 meV). 56 To our knowledge, experimental studies of other acceptor impurities have only been performed using ion implantation (see, e.g., Ref.…”
Section: Alternative Acceptorsmentioning
confidence: 84%
“…For such applications it is necessary to dope these semiconductors, and, commonly, Si or O are used as donors, 20,21 and Mg, Be, Zn, or Ca as acceptors. 17,[22][23][24][25][26][27] The incorporation of dopants into gallium nitride ͑GaN͒ and aluminum nitride ͑AlN͒ by diffusion is very difficult due to their high thermal stability. [28][29][30] Moreover, the realization of lateral doping structures during film growth is impossible.…”
Section: Ion Implanted Dopants In Gan and Aln: Lattice Sites Annealimentioning
confidence: 99%
“…This conclusion is in agreement with the assessment of Bernardini et al 6 Experiments on Be incorporation in GaN are still scarce. Incorporation of Be in GaN has so far been performed during MBE growth [7][8][9][10][11][12][13][14][15] and using ion implantation. 16,17 The earliest report of Be doping was by Ilegems and Dingle, 47 who incorporated Be during vapor growth of GaN.…”
Section: A Incorporation Of Be In Ganmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] These experimental studies have involved both wurtzite and cubic phases of GaN; the cubic phase can be obtained by growth on cubic substrates, under appropriately tailored conditions. Another technique for Be incorporation that has been attempted is ion implantation.…”
Section: Introductionmentioning
confidence: 99%